Polyoxometalates for photocatalytic degradation of aqueous dyestuff solutions and quantitative structure–property relationship study on photolysis rate constants. Issue 3 (16th March 2017) - Zhu, Xiuhua; Sheng, Feng; Wang, Wei; Shi, Fuyou; Ding, Guanghui; Zhang, Rong; Wang, Pengyuan
ABSTRACT: Polyoxometalate, K6 TiW11 O39 Sn·7H2 O (TiW11 Sn), was synthesized and characterized. TiW11 Sn and K6 ZrW11 O39 Sn·12H2 O (ZrW11 Sn) were evaluated for their photocatalytic degradation of triarylmethane (brilliant green and acid blue 9), bisazo (C.I. reactive black 5), and monoazo dyestuffs (C.I. reactive red 24, C.I. reactive red 194, and C.I. reactive orange 5) with natural sunlight in homogeneous aqueous solutions. TiW11 Sn and ZrW11 Sn effectively and photocatalytically decolorized the dyestuffs. The TiW11 Sn- and ZrW11 Sn-mediated photocatalytic degradation of the dyestuffs involved a pseudo-first-order reaction and was modeled by Langmuir–Hinshelwood-type kinetics. The observed pseudo-first-order rate constants ( K / ) of triarylmethane dyestuffs were generally bigger than that of the azo dyestuffs. Quantitative structure–property relationship models of the K / of the dyestuffs were developed using partial least-square regression. The cumulative variance of the dependent variable explained by the partial least-square components was > 0.753 for each optimal model. This value indicated that the model had good predictive ability and robustness. The K / values of the dyestuffs were related to the energy of the lowest unoccupied molecular orbital, and the most positive net atomic charges on a sulfur atom of dyestuffs. The linear correlation coefficients between the predicted and experimental values were all > 0.9950.